2014
DOI: 10.1182/blood.v124.21.1114.1114
|View full text |Cite
|
Sign up to set email alerts
|

CS-1 Re-Directed Central Memory T Cell Therapy for Multiple Myeloma

Abstract: Multiple myeloma (MM), a plasma cell malignancy, accounts for approximately 1 percent of all cancers and slightly more than 10 percent of hematologic malignancies in the United States. Approximately 20,000 new cases will be diagnosed this year and over 11,000 people will die from this disease. Current therapies for MM often induce remission, but nearly all patients eventually relapse and die. T-cell mediated anti-tumor therapies using genetically modify T cells with specific chimeric antigen receptors (CARs) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The authors hypothesised that lymphocytic fratricide by SLAMF7-CAR T cells might lead to acute and chronic side effects such as cytokine storm and viral infections, when used in a clinical setting. 51,52 Wang et al 53 also reported on a SLAMF7-CAR encoded by a lentiviral vector and containing a CD28 co-stimulatory domain. Two mutations on the IgG4 linker CH-2 portion were introduced to enhance the potency and persistence of the SLAMF7-CAR T cells.…”
Section: Car T Cells In the Treatment Of MMmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors hypothesised that lymphocytic fratricide by SLAMF7-CAR T cells might lead to acute and chronic side effects such as cytokine storm and viral infections, when used in a clinical setting. 51,52 Wang et al 53 also reported on a SLAMF7-CAR encoded by a lentiviral vector and containing a CD28 co-stimulatory domain. Two mutations on the IgG4 linker CH-2 portion were introduced to enhance the potency and persistence of the SLAMF7-CAR T cells.…”
Section: Car T Cells In the Treatment Of MMmentioning
confidence: 99%
“…These promising results support the suitability of SLAMF7-CARs for further evaluation in early-phase clinical trials. 53 Furthermore, in terms of a potential universal ‘off-the-shelf’ approach, Galetto et al 54 and Mathur et al 55 designed allogeneic SLAMF7-CAR T cells derived from healthy donor peripheral blood mononuclear cells (PBMCs). As TCR-deficient T cells were demonstrated not to mediate alloreactivity in a xenograft-versus-host disease (GvHD) mouse model, the TCRα constant ( TRAC ) gene was inactivated to reduce the GvHD potential of the allogeneic SLAMF7-CAR T cells.…”
Section: Car T Cells In the Treatment Of MMmentioning
confidence: 99%